2014
DOI: 10.1038/ncomms4663
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of charge transfer and redistribution in LaAlO3/SrTiO3 revealed by high-energy optical conductivity

Abstract: In condensed matter physics the quasi two-dimensional electron gas at the interface of two different insulators, polar LaAlO3 on nonpolar SrTiO3 (LaAlO3/SrTiO3) is a spectacular and surprising observation. This phenomenon is LaAlO3 film thickness dependent and may be explained by the polarization catastrophe model, in which a charge transfer of 0.5e(-) from the LaAlO3 film into the LaAlO3/SrTiO3 interface is expected. Here we show that in conducting samples (≥ 4 unit cells of LaAlO3) there is indeed a ~0.5e(-)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
100
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(117 citation statements)
references
References 57 publications
(186 reference statements)
13
100
1
Order By: Relevance
“…Band structure studies imply that the lattice distortion due to ionic relaxations are more at the outer layers of LaAlO 3 film that are adjacent to the SrTiO 3 and to the air; the distortion decreases and eventually vanishes as the thickness of LaAlO 3 is increased [22,23]. Further the electron carrier density measured by optical conductivity studies was found to agree with the value predicted by PCM [20,21], which supports the validity of PCM.…”
Section: Polar Catastrophe Model (Pcm)supporting
confidence: 76%
See 1 more Smart Citation
“…Band structure studies imply that the lattice distortion due to ionic relaxations are more at the outer layers of LaAlO 3 film that are adjacent to the SrTiO 3 and to the air; the distortion decreases and eventually vanishes as the thickness of LaAlO 3 is increased [22,23]. Further the electron carrier density measured by optical conductivity studies was found to agree with the value predicted by PCM [20,21], which supports the validity of PCM.…”
Section: Polar Catastrophe Model (Pcm)supporting
confidence: 76%
“…However, there exists a threshold thickness (3 unit cells) of LaAlO 3 , above which the metallic conductivity was observed [2,19]. From optical studies, it was shown that up to the thickness of 3 unit cells, the transferred electrons are trapped in the localized states of interface created by lattice distortion [20,21]. Band structure studies imply that the lattice distortion due to ionic relaxations are more at the outer layers of LaAlO 3 film that are adjacent to the SrTiO 3 and to the air; the distortion decreases and eventually vanishes as the thickness of LaAlO 3 is increased [22,23].…”
Section: Polar Catastrophe Model (Pcm)mentioning
confidence: 99%
“…Reinterpretation of the puzzle: According to Gauss' law, the experimentally observed weak electric field in LaAlO 3 film means that the total external charge density (mobile and/or immobile) at the interface must be B0.5e S 2D À 1 (Supplementary Note 7), as recently observed 55 . For n LAO oL c , there is no interfacial conductivity and thus none of these interfacial charge contribute to the conductivity.…”
Section: Articlementioning
confidence: 94%
“…Most groups assume the surface to be AlO 2 -terminated by counting RHEED intensity oscillations during growth. 12,20 However, the surface termination and its structure may change upon exposure to conditions under which the 2DEG properties are measured.…”
Section: Introductionmentioning
confidence: 99%